Toughened magnesium oxysulfate board and preparation method thereof
By adding specific insulation additives and modifiers to the slurry of magnesium sulfide plates, the problems of high density and poor insulation effect of magnesium sulfide plates are solved, and lightweight toughened magnesium sulfide plates are produced, achieving good thermal insulation performance, flame retardancy and flexural strength.
Patent Information
- Application Number
- CN202411829710.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The existing magnesium sulfide and oxidation board has a high density, which increases the structural load burden and installation difficulty, and has poor insulation effect. It is easy to cause the strength and toughness of the board to decrease when the insulation particles are added.
By adding phenolic foam powder, hollow glass microbeads and floating beads to the slurry as heat insulating additives, combining a sprinkler and a hydrophilic modifier, the density and thermal conductivity of the plate are adjusted, and the dispersion of polypropylene fibers and the hydrophobicity of the floating beads are improved, and light toughened sulfhydryl magnesium oxidation plates are prepared.
It realizes lightweight magnesium sulfide and magnesium sulfide plates with good thermal insulation performance, flame retardancy and structural stability, which reduces the density and thermal conductivity of the plates, and improves the flexural strength and toughness of the plates.
Smart Images

Figure BDA0005185268190000101 
Figure BDA0005185268190000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a toughened magnesium oxysulfate board and a preparation method thereof. Background Art
[0002] Magnesium oxysulfide board is a high-strength, heat-resistant and fire-resistant inorganic material, which is widely used in wall panels, insulation boards, fire-resistant components, ventilation ducts and other fields. However, the high density increases the structural load burden and installation difficulty, and the thermal insulation effect is not good. When adding thermal insulation particles, it is easy to cause the strength and toughness of the board to decrease.
[0003] Therefore, it is necessary to improve the magnesium oxysulfide board in the prior art. Summary of the invention
[0004] One of the purposes of the present invention is to overcome the defects in the prior art and provide a lightweight toughened magnesium oxysulfide board with good thermal insulation performance, flame retardancy, structural stability and flexural resistance.
[0005] In order to achieve the above-mentioned process effect, the technical scheme of the present invention is: a toughened magnesium oxysulfide board, wherein the slurry of the toughened magnesium oxysulfide board comprises, by weight, 100 parts of magnesium oxide, 110-140 parts of magnesium sulfate aqueous solution, 1-4 parts of polypropylene fiber, 2-5 parts of dispersing agent, 2-5 parts of hydrophilic modifier, 5-10 parts of filler, 25-45 parts of thermal insulation additive, 4-8 parts of curing modifier and 2-8 parts of foaming agent;
[0006] The heat insulation additives include phenolic foam powder, hollow glass microspheres and floating beads;
[0007] The dispersing agent comprises first polyvinyl chloride particles with a particle size of 1 to 1.5 mm and second polyvinyl chloride particles with a particle size of 1 to 2 μm, and the mass of the first polyvinyl chloride particles and the second polyvinyl chloride particles is (2 to 3): 1;
[0008] The hydrophilic modifier is a hydrophilic polymer containing hydroxyl groups and amino groups.
[0009] The preferred technical solution is: the preparation of the hydrophilic modifier is: 3-(2,3-epoxypropoxy)propyltrimethoxysilane and polyethyleneimine are dissolved in an ethanol solution and reacted at a temperature of 50 to 60°C to obtain a first reaction liquid, dopamine is dissolved in a buffer solution prepared by tris(hydroxymethyl)aminomethane and hydrochloric acid solution to obtain a second reaction liquid, the first reaction liquid and the second reaction liquid are reacted at a temperature of 25 to 30°C, and the pH of the buffer solution is 8.2 to 8.7.
[0010] The preferred technical solution is: the weight average molecular weight of the polyethyleneimine is 600-700, the concentration of 3-(2,3-epoxypropoxy)propyltrimethoxysilane in the first reaction liquid is 5-10 g / L, and the molar ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to polyethyleneimine is 1:(0.5-1); the content of dopamine in the second reaction liquid is 3-6 g / L, and the volume ratio of the first reaction liquid to the second reaction liquid is 1:(1-2).
[0011] The preferred technical solution is: the mass ratio of the phenolic foam powder, the hollow glass microspheres and the floating beads is (3-10): (3-10): (19-25).
[0012] The preferred technical solution is: the curing modifier is a mixed solution of phosphate, organic acid, inorganic acid and water, and the mass ratio of the phosphate, organic acid, inorganic acid and water is (10-15): (40-60): (2-8): 100.
[0013] The preferred technical solution is: the particle size of the phenolic foam powder is 100-200 mesh; the particle size of the hollow glass microspheres is 50-150 μm; the particle size of the floating beads is 100-250; and the diameter of the polypropylene fiber is 5-20 mm.
[0014] The preferred technical solution is: the Baume degree of the magnesium sulfate aqueous solution is 25 to 30 degrees.
[0015] The preferred technical solution is: the foaming agent is an animal protein foaming agent.
[0016] The second object of the present invention is to overcome the defects existing in the prior art and provide a method for preparing a toughened magnesium oxysulfate board, comprising the following steps:
[0017] S1: preparing a mold, on which a substrate is arranged;
[0018] S2: Slurry preparation of magnesium sulfate board: first prepare magnesium sulfate aqueous solution in a stirring kettle, add dispersant and stir, then add polypropylene fiber to disperse, add hydrophilic modifier, add floating beads in the reaction, then after sufficient reaction, mix magnesium oxide, remaining thermal insulation additives and curing modifier according to proportion, finally add foaming agent and stir evenly;
[0019] S3: The uniformly mixed slurry is applied to the surface of the substrate for preliminary forming to obtain a magnesium oxysulfide sheet body;
[0020] S4: the embryo is divided into blocks and distributed to a molding frame for the first curing to obtain a magnesium oxysulfide board matrix;
[0021] S5: The magnesium oxysulfide board substrate is demoulded and cured for the second time to obtain the magnesium oxysulfide board.
[0022] The preferred technical solution is: the temperature of the first curing is 30-40°C, and the temperature of the second curing is 40-50°C.
[0023] The advantages and beneficial effects of the present invention are:
[0024] The density and thermal conductivity of the board are adjusted by using a combination of phenolic foam powder, hollow glass microspheres and floating beads to produce a lightweight magnesium oxysulfide board with good thermal insulation performance, flame retardancy and structural stability.
[0025] The dispersibility of the polypropylene fiber is improved by using the dispersant and the hydrophilic modifier, thereby obtaining a toughened magnesium oxysulfate board, and the hydrophobicity of the floating beads is improved, thereby further obtaining a lightweight magnesium oxysulfate board. DETAILED DESCRIPTION
[0026] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.
[0027] model
[0028] Magnesium oxide was purchased from Liaoning Renxiang Refractory Materials Co., Ltd.;
[0029] Magnesium sulfate was purchased from Lianyungang Toyota Biotechnology Co., Ltd.;
[0030] Light calcium carbonate was purchased from Jiangxi Hengshengtai New Materials Co., Ltd.;
[0031] Hollow glass microspheres were purchased from Zhongke Huaxing New Materials Co., Ltd.;
[0032] The floating beads were purchased from Shijiazhuang Jiude Minerals Co., Ltd.
[0033] The foaming agent was purchased from Henan Yongli Building Materials Co., Ltd.;
[0034] Phosphoric acid was purchased from Yancheng Huaihai Phosphorus Products Co., Ltd.;
[0035] Citric acid was purchased from Yixing Xielian Biochemical Co., Ltd.;
[0036] Phosphate was purchased from Jinan Yeqing Biotechnology Co., Ltd.
[0037] Magnesium Oxide
[0038] Refers to lightly burned magnesium oxide, which is one of the components of magnesium oxysulfide cement binder. Its active magnesium oxide content is 85% to 92%, and its particle size is 75 to 90 μm. Magnesium oxide is an alkaline oxide and also an ionic compound. Magnesium oxide provides strength for magnesium materials. Magnesium oxide reacts in aqueous solution to form colloidal magnesium hydroxide, which forms a cement binder system with magnesium sulfate, and then provides excellent strength and wear resistance for magnesium materials after solidification.
[0039] Magnesium sulfate aqueous solution
[0040] It is also one of the components of magnesium oxysulfate cement cementitious materials. As a blending liquid for magnesium materials, magnesium sulfate aqueous solution does not contain halogens, effectively avoiding problems such as halogen return and corrosion of metal materials. Baume degree is a method of expressing solution concentration. The Baume degree of magnesium sulfate solution is 25-30 degrees. If the Baume degree of magnesium sulfate aqueous solution is too large, the water solvent will be reduced, the reactant magnesium oxide will be too much, and the fluidity of the slurry will deteriorate. The solidification time from wet slurry to hardened slurry is too fast, which is easy to cause concentrated heat release, resulting in magnesium material board expansion, deformation or warping; if the Baume degree of magnesium sulfate aqueous solution is too small, the water solvent will increase, and the excess water will reduce the concentration of magnesium ions and sulfate ions, and the contact probability of magnesium oxide hydration layer with magnesium ions and sulfate ions will be reduced, the amount of crystal generation and crystallinity will be reduced, and the strength of magnesium material board will be reduced. During the curing process, the excess water diffuses outward in the form of water vapor, forming a large number of pores inside the system, and the controllability of the porosity is poor.
[0041] filler
[0042] It is light calcium carbonate with a fineness of 1100-1250 mesh, mainly used to improve the strength of magnesium materials.
[0043] Thermal insulation additives
[0044] Including phenolic foam powder, hollow glass microspheres and floating beads. The particle size of phenolic foam powder is 100-200 mesh, the particle size of hollow glass microspheres is 50-150μm, and the particle size of floating beads is 100-250μm. Adding too much phenolic foam powder will have a negative effect on the strength of the magnesium material board, and adding too little will result in poor thermal insulation effect of the magnesium material board; adding too much hollow glass microspheres will have a negative effect on the stability of the magnesium material board, and adding too little will result in a high density and large structural load mass of the magnesium material board, which is not convenient for pipeline installation; adding too much floating beads will have a negative effect on the processing performance and appearance of the magnesium material board, and adding too little will have a negative effect on the strength and stability of the magnesium material board.
[0045] Preparation of phenolic foam powder: The phenolic foam boards that are defective or scrapped during production are reused, and the phenolic foam boards are crushed and sieved to screen out phenolic with a particle size of 100 to 200 meshes.
[0046] Dispersing agent
[0047] It includes first polyvinyl chloride particles with a particle size of 1 to 1.5 mm and second polyvinyl chloride particles with a particle size of 1 to 2 μm. The polyvinyl chloride material is selected to improve the water resistance and moisture resistance of the board, reduce the risk of water absorption and swelling, further increase the flexibility and impact resistance of the magnesium oxysulfide board, and make the board not easy to break or damage when subjected to external force. The mass of the first polyvinyl chloride particles and the second polyvinyl chloride particles is (2 to 3): 1. If the amount of the first polyvinyl chloride particles added is too small, the dispersibility of the polypropylene fiber, the second polyvinyl chloride particles and the small particle insulation additive is not good; if the amount of the first polyvinyl chloride particles added is too much, the compatibility with the magnesium oxysulfide matrix is poor and it is easy to deposit. The second polyvinyl chloride particles mainly attach to the surface of the floating beads to prevent the floating beads from absorbing water and reducing the thermal insulation effect and failing to reduce the weight of the magnesium oxysulfide board.
[0048] Hydrophilic modifier
[0049] Preparation method: 3-(2,3-epoxypropoxy)propyltrimethoxysilane and polyethyleneimine are dissolved in 100 ml ethanol solution and reacted at 50-60° C. to obtain a first reaction liquid, dopamine is dissolved in a buffer solution prepared by trishydroxymethylaminomethane and hydrochloric acid solution to obtain a second reaction liquid, and the first reaction liquid and the second reaction liquid are reacted at 25-30° C. to obtain the obtained product. The weight average molecular weight of polyethyleneimine is 600-700, the concentration of 3-(2,3-epoxypropoxy)propyltrimethoxysilane in the first reaction liquid is 5-10 g / L, and the molar ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to polyethyleneimine is 1:(0.5-1); the content of dopamine in the second reaction liquid is 3-6 g / L, the pH of the buffer solution is 8.2-8.7, and the volume ratio of the first reaction liquid to the second reaction liquid is 1:(1-2).
[0050] Adding too much of the first reaction liquid affects the self-polymerization of dopamine, reduces the amount and connection points of dopamine, affects the modification rate of the hydrophilic modifier and the polypropylene fiber, and reduces the amount of the second polyvinyl chloride particles connected to the surface of the beads by polydopamine. The water absorption of the beads is not well modified, resulting in a decrease in its thermal insulation effect. If the amount of the first reaction liquid added is too little, the self-polymerization of dopamine is too large, which can easily lead to the agglomeration of the highly viscous thermal insulation additive and the polypropylene fiber, and have a negative impact on the performance of the magnesium oxysulfide board.
[0051] Curing modifier
[0052] It is a mixed solution of phosphate, organic acid, inorganic acid and water. The mixed solutions act synergistically and have a retarding effect. The time from initial setting to final setting of the magnesium material board is controllable, which not only further improves the stability of the magnesium material board during the curing process, but also solves the problems of easy cracking and curling of the magnesium material board.
[0053] The phosphate is one or more of sodium dihydrogen phosphate, calcium hydrogen phosphate and potassium dihydrogen phosphate. Further, the phosphate is sodium dihydrogen phosphate. Phosphates improve the stability of the magnesium material board during the curing process, improve the strength of the magnesium material board, reduce the shrinkage rate of the magnesium material board, and improve the curling of the magnesium material board. If the amount of phosphate added is too much, the strength of the magnesium material board decreases and the shrinkage rate increases; if the amount of phosphate added is too little, pores are likely to appear on the surface of the magnesium material board.
[0054] Organic acids include, but are not limited to, oxalic acid, citric acid, and sulfosalicylic acid.
[0055] Inorganic acids include, but are not limited to, phosphoric acid.
[0056] Foaming agent
[0057] Plant protein foaming agents, animal protein foaming agents and high molecular weight composite foaming agents can be used. Furthermore, the foaming agent is an animal protein foaming agent. The bubbles produced by the animal protein foaming agent are more stable, the foam volume is large and the foam is fine.
[0058] The preparation method of toughened magnesium oxysulfate board comprises the following steps:
[0059] S1: preparing a mold, on which a first substrate composed of a glass fiber mesh cloth and a non-woven fabric is laid;
[0060] S2: Slurry configuration of magnesium oxysulfide board: prepare brine, first add dispersant and stir, then add polypropylene fiber to disperse, and add hydrophilic modifier, add floating beads in the reaction, then after sufficient reaction, mix magnesium oxide, magnesium sulfate aqueous solution, remaining insulation additives and curing modifier in proportion, and finally add foaming agent and stir evenly;
[0061] S3: The uniformly mixed slurry is coated on the first substrate of S1, and then a second substrate composed of a glass fiber mesh cloth and a non-woven fabric is covered on the slurry to preliminarily form a magnesium oxysulfide plate blank;
[0062] S4: The embryo is divided into blocks and distributed to a forming frame for the first curing to obtain a magnesium oxysulfide board matrix. During the first curing, curing is required. The first curing temperature is controlled at 30-40°C, the relative humidity is maintained at 60%-70%, and the curing time is 12-24h.
[0063] S5: The magnesium oxysulfide board substrate is demoulded and subjected to a second curing to obtain a magnesium material board, wherein the magnesium oxysulfide board substrates after demoulding are stacked layer by layer, and an interlayer board is arranged between the upper and lower adjacent magnesium oxysulfide board substrates; the temperature of the second curing is 40-50°C, and curing is also required during the second curing, and the second curing time is 2-4 days.
[0064] The magnesium oxysulfide board matrix still has a relatively high temperature after the first curing. The upper and lower adjacent magnesium material boards are formed with a heat dissipation gap through the interlayer board to prevent the local temperature from being too high. It is also beneficial to the volatilization of moisture between the upper and lower adjacent magnesium material boards, improving the efficiency of the second curing, and at the same time improving the structural stability and strength of the magnesium oxysulfide board.
[0065] The composite substrate of glass fiber mesh cloth and non-woven fabric improves the flexural strength of magnesium oxysulfide board.
[0066] According to the actual production specifications, the magnesium oxysulfide board is cut into unit magnesium oxysulfide boards, and the unit magnesium oxysulfide boards are compounded with steel panels through adhesive layers to further improve the mechanical strength, waterproofness and fire resistance of the magnesium oxysulfide boards.
[0067] Example 1
[0068] Calculated by mass, the slurry of the toughened magnesium oxysulfate board includes 100 parts of magnesium oxide, 120 parts of magnesium sulfate aqueous solution, 2 parts of polypropylene fiber, 4 parts of dispersing agent, 2 parts of hydrophilic modifier, 8 parts of light calcium carbonate, 35 parts of thermal insulation additive, 5 parts of curing modifier and 5 parts of foaming agent.
[0069] The heat-insulating additive includes phenolic foam powder, hollow glass microspheres and floating beads in a mass ratio of 5:5:23. The dispersant includes first polyvinyl chloride particles with a particle size of 1 to 1.5 mm and second polyvinyl chloride particles with a particle size of 1 to 2 μm, and the mass ratio of the first polyvinyl chloride particles to the second polyvinyl chloride particles is 2.5:1.
[0070] The preparation method of the hydrophilic modifier is as follows: 3-(2,3-epoxypropoxy)propyltrimethoxysilane and polyethyleneimine are dissolved in 100 ml of ethanol solution and reacted at 55°C to obtain a first reaction liquid, dopamine is dissolved in a buffer solution prepared by tris(hydroxymethyl)aminomethane and hydrochloric acid solution to obtain a second reaction liquid, and the first reaction liquid and the second reaction liquid are reacted at 25°C to obtain the first reaction liquid. The weight average molecular weight of polyethyleneimine is 600, the concentration of 3-(2,3-epoxypropoxy)propyltrimethoxysilane in the first reaction liquid is 8 g / L, and the molar ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to polyethyleneimine is 1:1; the content of dopamine in the second reaction liquid is 5 g / L, the mass fraction of the hydrochloric acid solution is 0.5%, the pH of the buffer solution is 8.5, and the volume ratio of the first reaction liquid to the second reaction liquid is 1:1.5.
[0071] The curing modifier is a mixed solution of phosphate, organic acid, inorganic acid and water in a mass ratio of 12:50:4:100.
[0072] The preparation method of toughened magnesium oxysulfate board comprises the following steps:
[0073] S1: preparing a mold, on which a first substrate composed of a glass fiber mesh cloth and a non-woven fabric is laid;
[0074] S2: The slurry of magnesium sulfate board is prepared according to the above proportion: first prepare magnesium sulfate aqueous solution in a stirring kettle, add a dispersant and stir, then add polypropylene fiber to disperse, and add a hydrophilic modifier, add floating beads during the reaction, and then after sufficient reaction, mix magnesium oxide, remaining thermal insulation additives and curing modifier according to proportion, and finally add a foaming agent and stir evenly;
[0075] S3: The uniformly mixed slurry is coated on the first substrate of S1, and then a second substrate composed of a glass fiber mesh cloth and a non-woven fabric is covered on the slurry to preliminarily form a magnesium oxysulfide plate blank;
[0076] S4: The embryo is divided into blocks and distributed to a molding frame, and the first curing is performed to obtain a magnesium oxysulfide board matrix. During the first curing, curing is required. The first curing temperature is controlled at 35°C, the relative humidity is maintained at 65%, and the curing time is 20 hours;
[0077] S5: The magnesium oxysulfide board substrate is demoulded and subjected to a second curing to obtain a magnesium material board, wherein the magnesium oxysulfide board substrates after demoulding are stacked layer by layer, and an interlayer board is arranged between the upper and lower adjacent magnesium oxysulfide board substrates; the temperature of the second curing is 45°C, and curing is also required during the second curing, and the second curing time is 3 days.
[0078] According to the actual production specifications, the magnesium oxysulfide board is cut into unit magnesium oxysulfide boards, and the unit magnesium oxysulfide boards are compounded with the steel panel through the adhesive layer. The length of the magnesium oxysulfide board is 3000mm*width 1200mm*thickness 14mm; the thickness of the steel panel is 0.3mm.
[0079] Example 2
[0080] Example 2 is based on Example 1, except that the composition of the hydrophilic modifier remains unchanged, and the volume ratio of the first reaction liquid to the second reaction liquid is 1:1.
[0081] Example 3
[0082] Example 2 is based on Example 1, except that the composition of the hydrophilic modifier remains unchanged, and the volume ratio of the first reaction liquid to the second reaction liquid is 1:3.
[0083] Comparative Example 1
[0084] Comparative Example 1 is based on Example 1, except that the slurry for toughening the magnesium oxysulfate board does not include a dispersing agent.
[0085] Comparative Example 2
[0086] Comparative Example 2 is based on Example 1, except that the dispersing agent only includes first polyvinyl chloride particles with a particle size of 1 to 1.5 mm.
[0087] Comparative Example 3
[0088] Comparative Example 3 is based on Example 1, except that the slurry for toughening the magnesium oxysulfate board does not include a hydrophilic modifier.
[0089] Comparative Example 4
[0090] Comparative Example 4 is based on Example 1, except that the thermal insulation additive only includes phenolic foam powder and hollow glass microspheres.
[0091] Comparative Example 5
[0092] Comparative Example 5 is based on Example 1, except that the thermal insulation additive only includes phenolic foam powder and floating beads.
[0093] Comparative Example 6
[0094] Comparative Example 6 is based on Example 1, except that the thermal insulation additive only includes hollow glass microspheres and floating beads.
[0095] Comparative Example 7
[0096] Comparative Example 7 is based on Example 1, except that the slurry for toughening the magnesium oxysulfate board does not include polypropylene fibers.
[0097] Comparative Example 8
[0098] Comparative Example 8 is based on Example 1, except that, in step S2 of the method for preparing the toughened magnesium oxysulfate board, a dispersant is first added and stirred, and then a hydrophilic modifier is added, and polypropylene fibers are added and dispersed, and the other sequences remain unchanged.
[0099] Comparative Example 9
[0100] Comparative Example 9 is based on Example 1, except that, in step S2 of the preparation method of the toughened magnesium oxysulfide board, a dispersant is first added and stirred, then polypropylene fibers are added and dispersed, and a hydrophilic modifier is added, and then after sufficient reaction, magnesium oxide, magnesium sulfate aqueous solution, thermal insulation additive and curing modifier are mixed in proportion, and floating beads are not added in the hydrophilic modifier reaction.
[0101] Performance test of toughened magnesium oxysulfate board:
[0102] 1. Density of magnesium oxysulfate board: test index GB / 7019-2014;
[0103] 2. Thermal conductivity: test index GB / 10294-2008;
[0104] 3. Flexural strength: test index GB / T17657-2013;
[0105] 4. Shrinkage rate: test index GB / 7019-2014;
[0106] 5. Halogen reversion: Testing index JC / 688-2006;
[0107] 6. Flame retardancy: test index GB / 8624-2012.
[0108] The performance test results of the toughened magnesium oxysulfide board of the embodiment and the comparative example are shown in the following table:
[0109]
[0110]
[0111] Compared with Example 1, the amount of the second reaction liquid in Example 3 increases, resulting in an increase in the amount of dopamine self-polymerization, which causes the highly viscous thermal insulation additive and the polypropylene fiber to agglomerate, which has a negative impact on the appearance, flexural strength and thermal insulation performance.
[0112] Compared with Example 1, the slurry of the toughened magnesium oxysulfate board in Comparative Example 1 does not include a dispersant, and the stirring speed and time need to be increased. Polypropylene fiber agglomeration still occurs, and the hydrophobic modification of the floating beads is poor, which leads to an increase in the density of the magnesium oxysulfate board and a decrease in the flexural strength.
[0113] Compared with Example 1, the hydrophobic modification of the floating beads in Comparative Example 2 is not good, which leads to an increase in the toughened magnesium oxysulfate board and a decrease in the flexural strength.
[0114] Compared with Example 1, Comparative Example 3 has a higher content of floating beads in the thermal insulation additive, and no hydrophilic modifier is added, resulting in poor hydrophobic modification, and the dispersion of polypropylene fibers is not improved, which has a negative impact on the density, flexural strength and thermal insulation performance of the magnesium oxysulfide board.
[0115] Compared with Example 1, the thermal insulation additives in Comparative Examples 4 to 6 do not include floating beads, which not only increases the cost of the combination, but also reduces the stability and flexural strength of the magnesium oxysulfide board; the thermal insulation additives do not include hollow glass microspheres, which has a negative impact on the density of the magnesium oxysulfide board, the structural load mass is large, and it is not convenient for the installation of pipelines; the thermal insulation additives do not include phenolic foam powder, which has a negative impact on the thermal insulation performance of the magnesium oxysulfide board.
[0116] Compared with Example 1, in Comparative Example 8, the order of adding the hydrophilic modifier and the polypropylene fiber is reversed, which is not conducive to the dispersion of the polypropylene fiber.
[0117] Compared with Example 1, the hydrophobic modification of the floating beads in Comparative Example 9 is not good, which has a negative impact on the density, flexural strength and thermal insulation performance of the magnesium oxysulfide board.
[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A toughened magnesium oxysulfate board, characterized in that: The slurry of the toughened magnesium oxysulfate board comprises, by weight, 100 parts of magnesium oxide, 110-140 parts of magnesium sulfate aqueous solution, 1-4 parts of polypropylene fiber, 2-5 parts of dispersing agent, 2-5 parts of hydrophilic modifier, 5-10 parts of filler, 25-45 parts of thermal insulation additive, 4-8 parts of curing modifier and 2-8 parts of foaming agent; The heat insulation additives include phenolic foam powder, hollow glass microspheres and floating beads; The dispersing agent comprises first polyvinyl chloride particles with a particle size of 1-1.5 mm and second polyvinyl chloride particles with a particle size of 1-2 μm, and the mass of the first polyvinyl chloride particles and the second polyvinyl chloride particles is (2-3): 1; The hydrophilic modifier is a hydrophilic polymer containing hydroxyl groups and amino groups.
2. The toughened magnesium oxysulfate board according to claim 1, characterized in that: The preparation of the hydrophilic modifier is as follows: 3-(2,3-epoxypropoxy)propyltrimethoxysilane and polyethyleneimine are dissolved in an ethanol solution and reacted at a temperature of 50-60° C. to obtain a first reaction liquid; dopamine is dissolved in a buffer solution prepared by tris(hydroxymethyl)aminomethane and a hydrochloric acid solution to obtain a second reaction liquid; the first reaction liquid and the second reaction liquid are reacted at a temperature of 25-30° C., and the pH of the buffer solution is 8.2-8.
7.
3. The toughened magnesium oxysulfate board according to claim 2, characterized in that: The weight average molecular weight of the polyethyleneimine is 600-700, the concentration of 3-(2,3-epoxypropoxy)propyltrimethoxysilane in the first reaction solution is 5-10 g / L, and the molar ratio of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to polyethyleneimine is 1:(0.5-1); the content of dopamine in the second reaction solution is 3-6 g / L, and the volume ratio of the first reaction solution to the second reaction solution is 1:(1-2).
4. The toughened magnesium oxysulfate board according to claim 1, characterized in that: The mass ratio of the phenolic foam powder, the hollow glass microspheres and the floating beads is (3-10): (3-10): (19-25).
5. The toughened magnesium oxysulfate board according to claim 1, characterized in that: The curing modifier is a mixed solution of phosphate, organic acid, inorganic acid and water, and the mass ratio of the phosphate, organic acid, inorganic acid and water is (10-15): (40-60): (2-8):
100.
6. The toughened magnesium oxysulfate board according to claim 1, characterized in that: The particle size of the phenolic foam powder is 100-200 meshes; the particle size of the hollow glass microspheres is 50-150 μm; the particle size of the floating beads is 100-250; and the diameter of the polypropylene fiber is 5-20 mm.
7. The toughened magnesium oxysulfate board according to claim 1, characterized in that: The Baume degree of the magnesium sulfate aqueous solution is 25 to 30 degrees.
8. The toughened magnesium oxysulfate board according to claim 1, characterized in that: The foaming agent is an animal protein foaming agent.
9. A method for preparing a toughened magnesium oxysulfate board, characterized in that: The following steps are involved: S1: preparing a mold, on which a substrate is arranged; S2: Slurry preparation of magnesium sulfate board: first prepare magnesium sulfate aqueous solution in a stirring kettle, add dispersant and stir, then add polypropylene fiber to disperse, add hydrophilic modifier, add floating beads in the reaction, then after sufficient reaction, mix magnesium oxide, remaining thermal insulation additives and curing modifier according to proportion, finally add foaming agent and stir evenly; S3: The uniformly mixed slurry is applied to the surface of the substrate for preliminary forming to obtain a magnesium oxysulfide sheet body; S4: the embryo body is divided into blocks and distributed to a molding frame for the first curing to obtain a magnesium oxysulfide board matrix; S5: The magnesium oxysulfide board substrate is demoulded and cured for the second time to obtain the magnesium oxysulfide board.
10. The method for preparing the toughened magnesium oxysulfate board according to claim 9, characterized in that: The temperature of the first curing is 30-40°C, and the temperature of the second curing is 40-50°C.